PATIENTS WITH DRY EYE ADMITTED TO AN INTENSIVE CARE UNIT - Danielly Oliveira Pitombeira; Ângela Monic Lima de Souza; Ana Paula Nunes de Lima Fernandes; Jéssica Naiara de Medeiros Araújo; Amanda Barbosa da Silva; Allyne Fortes Vitor (Universidade Federal do Paraná, 2018)
Objective: to identify clinical and sociodemographic characteristics of patients with dry eye admitted to an intensive care unit. Method: observational and descriptive study with a quantitative approach conducted in a university hospital from January to June 2016, through the use of a form with questions on sociodemograpic characteristics and clinical data related to dry eye. After diagnostic inference, a sample of 108 patients was obtained. Descriptive analyzes, association measures and prevalence ratios were performed with the use of a statistical package. Results: there was a prevalence of male patients (53.7%), mean age of 57 years; 61 (56.6%) with hypertension; 84 (77.8%) with complete closure of the eyelid in the right eye and 80 (74.1%) with complete eyelid closure in the left eye; 44 (40.7%) with right eye hyperemia and 41 (38%) with left eye hyperemia. Schirmer test detected a reduced tear volume, median of 3 mm in the right eye and 4 mm in the left eye. Conclusion: Relevant information for the characterization of patients with dry eye, prediction of the phenomenon and delivery of proper care was identified.